A state of educational imbalance: an autoethnographic account of a deputy commissioner facilitating educational reform - Neuenswander, Brad (Kansas State University, 2018)
This dissertation presents autoethnographic narrative of my experience as the Deputy Commissioner of Education in Kansas while I was working to change how schools in Kansas are accredited to achieve better educational outcomes for students who were traditionally being left behind. Two types of data informed the study: tour data, and narrative data. Tour data refer to input that was gathered in 2015 during a 27-city tour across Kansas where the Commissioner of Education and myself asked three key questions to over 2,000 Kansans who attended these tour events. The responses were documented where attendants represented various stakeholder positions regarding educating Kansans. Upon completion of the first tour, the data were analyzed. To verify accuracy of the interpretation of the data, we organized a second tour to share results with stakeholders. Finalizing findings from stakeholder feedback, the State Board of Education set a new vision for educational reform in the state of Kansas. The second type of data informing this study is narrative data that shape the autoethnography. The purpose of this autoethnography is to highlight and connect critical narratives from my positionality of a Deputy Commissioner of the Kansas Department of Education, juxtaposed against state and local culture of public education that contributed to a new Kansas accreditation model. The autoethnography is broadly informed by narrative inquiry and writing as a form of analysis and inquiry. The critical narratives offer a historical documentation of the processes that influenced an educational reform in Kansas when such reform had its own political and logistical challenges. Without a narrative telling of the events that led to a new educational vision and accreditation model for Kansas, important conversations, thoughts and studies would be lost, and questions would go unanswered as to how Kansas developed its new vision and direction. Two broad insights emerged as a result of engaging in this study. First, the tour data informed us that, as an educational system, the model that holds schools accountable to students and communities is out-of-balance with the desires of Kansans. Unless educational leaders and policy makers change the accountability model for schools and students, it is not likely that the educational system will see any significant change in the current educational results and outcomes equitably for those students who are traditionally left behind. Second, by writing the autoethnographic narrative, I was able to trace my upbringing, advantages that I enjoyed, and the responsibilities that come with such advantages. Being from a family of educational leaders and adhering to a belief system instilled by my father regarding equity-based learning for all, the autoethnographic narrative allowed me to stay open to information that I might not have known from my advantageous position as I toured through the state. Further, focusing on the various roles that I play within Kansas such as being a federal liaison and state department educational leader, I engaged in deep listening during the tours to facilitate a responsive educational reform that highlight voices that might have been traditionally unheard or silenced.
Keywords: Educational Reform in Kansas